Analysis of Shadow Effect on Solar PV Plant using Helioscope Simulation Technology in Palipi Village - Rahmaniar Rahmaniar; Khairul Khairul; Agus Junaidi; Debby Keumala Sari (Universitas Negeri Padang, 2023)
This research discusses the study of renewable energy potential in Palipi village, North Sumatra Province, renewable energy is an option in overcoming the problem of irrigating rice fields in Palipi village in the summer. The use of pumps in irrigation in Palipi Village, North Sumatra province for six hours requires 138,564 watts of electrical energy per day. Solar potential is the most feasible as an option in renewable energy development, through solar power plants. The research method uses a simulation of solar energy potential by determining the number of solar panels used in the electricity generation process. HelioScope was used as an assistive technology tool to find the maximum utilisation of the available space, the influence of shadows on solar panels was also taken into account for the feasibility study conducted. The total electrical energy obtained through PLTS generation in Palipi village is 10,345.5 kWh/year, with the largest loss of 13% influenced by temperature, while the shadow effect contributes to a loss of 0.9% due to the shadow factor of 1 building and an electricity tower pole at the location of the solar panel.